If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3g = -7 + 4g Solving 3g = -7 + 4g Solving for variable 'g'. Move all terms containing g to the left, all other terms to the right. Add '-4g' to each side of the equation. 3g + -4g = -7 + 4g + -4g Combine like terms: 3g + -4g = -1g -1g = -7 + 4g + -4g Combine like terms: 4g + -4g = 0 -1g = -7 + 0 -1g = -7 Divide each side by '-1'. g = 7 Simplifying g = 7
| 9(t-5)+6t=5(3t+4)-10 | | m=-0.4n+28 | | y+y-y-y+y-1=18 | | -93-4v=-10v+3 | | 2x^4-9x^2-16x=0 | | 3h+3h-6h+2j-2=12 | | 2x^4-9x^2-16=0 | | 18j+2j-10j-5j-4j=16 | | 18j+2j-10-5j-4j=16 | | 13p-6p-5p=18 | | 9t+(3f)t+13= | | 27-×/4=x/5 | | 4+7x-3=9x+13-6x | | 6j+-2j+14j-7j+-9n-(-19)=-15 | | m(a+5)=Kfora | | -0.1x^2-x+31=0.1x^2+2x+11 | | 6j+-2j+14j-7j+-9-(-19)=-15 | | 0.2x^2+x-20=0 | | 6j+-2j+14j-7j+(-19)=-15 | | 6j+2j+14j-7j+(-19)=-15 | | r-r+5r-2r=9 | | -5c+14c+-7=11 | | 5b-19b-(-20b)-(-14)=-10 | | 32+0.90m=2(31+0.30m) | | 20m-10m+2m-8m+2m=6 | | 5u+4u-6u-u=12 | | n^2-n-480=0 | | log(base)2(x^2-3x-66)=2 | | 20n-12n+-9n=8 | | 2x=17+2 | | -3h+-h+6h+-7h=15 | | 5x+26=10x-10 |